The Live peak: the pandemic on Jair Bolsonaro’s Live Broadcastings - Aggio, Camilo (2022)
This article aims at analyze Jair Bolsonaro live broadcasts on his social networks accounts during the first peak of the Covid-19 pandemic in Brazil. We access and discuss how the theme of Covid-19 was considered by the Brazillian president at a time of upsurge of the pandemic until then unprecedented. The results show that Covid-19 is the most discussed topic, although the term “pandemic” is not part of the president's repertoire. The approaches identified in his comments on the current health crisis configure a discourse marked by denial and the dissemination of misinformation and conspiracy theories in the public arena.